2018
DOI: 10.1016/j.scitotenv.2017.12.299
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact of natural organic ligands on the colloidal stability of silver nanoparticles

Abstract: Interaction of natural organic matter (NOM) with engineered nanoparticles (NPs) determine NP fate, transport, and environmental persistence. However, the effect of NOM chemical composition, structure, and concentration on aggregation kinetics and dissolution behavior of silver nanoparticles (AgNPs) are still poorly understood because of heterogeneity and variability in NOM and AgNP properties. Here, aggregation behavior of citrate-coated silver nanoparticles (cit-AgNPs with a z-average diameter of 18nm) was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…In the rich environment of marine salts, specific ions might have specific chemical interactions with surface groups and thus neutralize particle charges (Hofmeister, 1888). In addition, Afshinnia et al (2018) reported that natural colloids from the medium (e.g., humic substances) could influence the charge of the particles, suppressing the positive charge and enhancing the negative one, depending on both the point zero charge (pzc) of the particles and the pH of the solution. An ecocorona can favor the adhesion of the particles to each other or instead reduce their flocculation in accordance with new surface affinities (Yu et al, 2017).…”
Section: Particle Charges In Seawatermentioning
confidence: 99%
“…In the rich environment of marine salts, specific ions might have specific chemical interactions with surface groups and thus neutralize particle charges (Hofmeister, 1888). In addition, Afshinnia et al (2018) reported that natural colloids from the medium (e.g., humic substances) could influence the charge of the particles, suppressing the positive charge and enhancing the negative one, depending on both the point zero charge (pzc) of the particles and the pH of the solution. An ecocorona can favor the adhesion of the particles to each other or instead reduce their flocculation in accordance with new surface affinities (Yu et al, 2017).…”
Section: Particle Charges In Seawatermentioning
confidence: 99%
“…The behaviour of NPs in test systems is not predictable using the traditional methods of partitioning and bioavailability [22,66]. The stability of organic-coated AgNPs in biological media has received significant attention in the last few years in nanotechnology and toxicology studies [3,84]. Similar to the observations made in this study, other toxicological studies also have shown that aggregation, dissolution, change in NP characteristics and culture media influence the bioavailability of NPs and hence, play an important role in determining toxicity [37,86,106].…”
Section: Agnp Stability and Dissolutionmentioning
confidence: 99%
“…The values of the effective aggregation rates and fractal structure parameters could, in principle, be obtained in the laboratory from aggregation experiments performed in synthetic solutions, as explained below. Several important contributions have been recently presented on the effect of natural dissolved organic matter (DOM) on the stability behaviour of NPs in samples representative of environmental conditions (Afshinnia et al, 2018;Baalousha et al, 2013a;Ellis et al, 2016) However, the specific role of the organic coating composition in the interactions of NPs with DOM still remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%